Investing in Energy or ICT for more Productivity in Algeria - Belghomari , Wassila (Finance and Business Economies Review, 2023)
This study aims to analyze and highlight the impact of investment in information, communication technology and energy on the total productivity of the industrial sector in Algeria. It is considered one of the most important elements of economic growth for governments and institutions with their various tasks. This is as a way to catch up with globalization and achieve economic integration by strengthening the connection to global communication networks, along with the access to energy sources for industry. As we have concluded a broader concept of investment in the technology sector, the energy sector through Addressing a standard study to find out the impact of each of them on productivity and comparing the results to reach a conclusion in order to come up with important recommendations on the subject. It should therefore be noted that investment in information and communication technologies will benefit the overall productivity of the industrial sector, we recommend encouraging foreign investment in the sector field of energy, because giant and pioneering companies are able to bear the costs of this type of investment. As for internal investments, we recommend directing them towards the information and communication technologies sector, particularly encouraging emerging companies in this field.